Mental models and pragmatics: Author's response - BYRNE, RUTH MARY JOSEPHINE (Cambridge University Press, 2000)
Van der Henst argues that the theory of mental models lacks a pragmatic component. He fills the gap with the notion that reasoners draw the most relevant conclusions. We agree, but argue that theories need an element of ?nondeterminism.? It is often impossible to predict either what will be most relevant or which particular conclusion an individual will draw.
PUBLISHED
Keywords: Psychology